Protective effects of melatonin against the toxic effects of environmental pollutants and heavy metals on testicular tissue: A systematic review and meta-analysis of animal studies - Dehdari Ebrahimi, Niloofar; Parsa, Shima; Nozari, Farnoosh; Shahlaee, Mohammad Amin; Maktabi, Amirhossein; Sayadi, Mehrab; Sadeghi, Alireza; Azarpira, Negar (Frontiers in Endocrinology, 2023)
Background Environmental pollution and infertility are two modern global challenges that agonize personal and public health. The causal relationship between these two deserves scientific efforts to intervene. It is believed that melatonin maintains antioxidant properties and may be utilized to protect the testicular tissue from oxidant effects caused by toxic materials. Methods A systematic literature search was conducted in PubMed, Scopus, and Web of Science to identify the animal trial studies that evaluated melatonin therapy’s effects on rodents’ testicular tissue against oxidative stress caused by heavy metal and non-heavy metal environmental pollutants. Data were pooled, and standardized mean difference and 95% confidence intervals were estimated using the random-effect model. Also, the risk of bias was assessed using the Systematic Review Centre for Laboratory animal Experimentation (SYRCLE) tool. (PROSPERO: CRD42022369872) Results Out of 10039 records, 38 studies were eligible for the review, of which 31 were included in the meta-analysis. Most of them showed beneficial effects of melatonin therapy on testicular tissue histopathology. [20 toxic materials were evaluated in this review, including arsenic, lead, hexavalent chromium, cadmium, potassium dichromate, sodium fluoride, cigarette smoke, formaldehyde, carbon tetrachloride (CCl4), 2-Bromopropane, bisphenol A, thioacetamide, bisphenol S, ochratoxin A, nicotine, diazinon, Bis(2-ethylhexyl) phthalate (DEHP), Chlorpyrifos (CPF), nonylphenol, and acetamiprid.] The pooled results showed that melatonin therapy increased sperm count, motility, viability and body and testicular weights, germinal epithelial height, Johnsen's biopsy score, epididymis weight, seminiferous tubular diameter, serum testosterone, and luteinizing hormone levels, testicular tissue Malondialdehyde, glutathione peroxidase, superoxide dismutase, and glutathione levels. On the other hand, abnormal sperm morphology, apoptotic index, and testicular tissue nitric oxide were lower in the melatonin therapy arms. The included studies presented a high risk of bias in most SYRCLE domains. Conclusion In conclusion, our study demonstrated amelioration of testicular histopathological characteristics, reproductive hormonal panel, and tissue markers of oxidative stress. Melatonin deserves scientific attention as a potential therapeutic agent for male infertility. Systematic review registration https://www.crd.york.ac.uk/PROSPERO, identifier CRD42022369872.